PROFIL KEMAMPUAN DECODING MEMBACA PERMULAAN BERDASARKAN TES EARLY GRADE READING ASSESSMENT (EGRA) PESERTA DIDIK KELAS I SDN 6 SELONG - Ulya, Manzilatul; Rahman Hakim, Arif; Nadiatul Soleha, Ria; Parsyillah Minallah, Ninda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the early reading decoding ability of Grade I students at SD Negeri 6 Selong in the academic year 2025/2026 across six aspects: letter recognition, letter sounds, syllable reading, word reading, reading accuracy, and reading fluency. The study employed a quantitative descriptive approach with all 23 Grade I students (14 male and 9 female) as subjects through total sampling technique. The instrument used was the Decoding Ability Assessment Sheet based on the Early Grade Reading Assessment (EGRA) with a maximum total score of 24. Raw scores for each aspect were converted to a 0–4 scale and categorized as: very good (19-24), good (13-18), fair (7-12), and poor (0-6). the results show that the average total decoding score was 15.21/24, classified as good. by aspect, letter recognition achieved the highest average (3.04/4.00-good), followed by letter sounds (2.92-good), syllable reading (2.64-good), reading accuracy (2.36-fair), word reading (2.35-fair), and reading fluency as the lowest (2.09-fair). category distribution revealed 7 students (30.43%) very good, 9 students (39.13%) good, 4 students (17.39%) fair, and 3 students (13.04%) poor. students in the Poor and Fair categories need systematic phonics-based remedial programs, while those in the Good and Very Good categories can be further developed through repeated reading programs to enhance fluency.